2008
DOI: 10.1089/cpb.2007.0157
|View full text |Cite
|
Sign up to set email alerts
|

Race, Gender, and Information Technology Use: The New Digital Divide

Abstract: This research examined race and gender differences in the intensity and nature of IT use and whether IT use predicted academic performance. A sample of 515 children (172 African Americans and 343 Caucasian Americans), average age 12 years old, completed surveys as part of their participation in the Children and Technology Project. Findings indicated race and gender differences in the intensity of IT use; African American males were the least intense users of computers and the Internet, and African American fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
177
2
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(195 citation statements)
references
References 11 publications
8
177
2
8
Order By: Relevance
“…In a study carried out on Korean children, it was found that possibility of playing online game among male children was higher than female children (Lee & Chae, 2007). Similar results were found in another study (Jackson, 2008). Frequency of watching TV is not effective in Internet use of male children.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…In a study carried out on Korean children, it was found that possibility of playing online game among male children was higher than female children (Lee & Chae, 2007). Similar results were found in another study (Jackson, 2008). Frequency of watching TV is not effective in Internet use of male children.…”
Section: Discussionsupporting
confidence: 56%
“…Jackson, Ervin, Gardner and Schmitt (2001) predicted and found that females used e-mail more than did males, males used the Web more than did females, and females reported more computer anxiety, less computer self-efficacy, and less favorable and less stereotypic computer attitudes. Jackson et al (2008) Vol. 8, No.…”
Section: Literatur Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, males are more likely to use digital media as tools for information and entertainment, whereas females tend to use them as tools for communication. 62 Controlling for gender, therefore, might have enhanced the validity of the study findings by verifying that the experimental results were solely due to the variation in screen size.…”
Section: Effects Of Screen Size On Smartphone Adoption 469mentioning
confidence: 78%
“…Although recent data regarding Internet access and types of Internet use is available (e.g., Jackson et al, 2008), to our knowledge, there is no academic research concerning Internet skills and their division over different races among populations at large.…”
Section: 5 I N E Q U a L I T Y A M O N G W H O M ?mentioning
confidence: 99%